Rancang Bangun Aplikasi Marketplace Digital Tanah Berbasis Sistem Informasi Geografis - Eris Elviana Julaida; Auliaputri Salsabila, Azka; Heriza Fiandini, Putri; Ardian Saputra, Dani; Naufal Adittama, Rafli (Sekolah Tinggi Pertanahan Nasional, 2024)
The public often faces challenges in land transactions due to limited access to information. This study develops a digital land marketplace application based on Geographic Information System (GIS), named